Ghosts of the Past in the Present in the Narratives of Diaspora - Katawal, Ubaraj (Literary Studies, 2020)
Eva Hoffmann, the Polish-American author, writes, “In our current, habitually diasporic, habitually nomadic world, the oppositional, bipolar model no longer holds” (Aciman 55). How does the past-present continuum work in this “habitually nomadic” experience? Can diasporic people forget the past as another country, or is it the present that is more foreign? How do the narratives of diaspora dramatize the past-present dynamic, and how do memories of the past affect the present?